Operating Policies in Multiechelon Dual-Constraint Job Shops - Fryer, John S. (Management Science, 1973)
In this paper a simulation study to examine the effects of operating policies on the performance of a multiechelon dual-constraint job shop is described. A hypothetical shop in which machines and workers are constraining resources is the setting of the study. The shop consists of divisions comprised of work centers which, in turn, contain machines to which workers are assigned. There are fewer workers than machines. Operating policies consist of rules for dispatching and labor control. There are two levels of labor control—decision rules are used for allocating workers to divisions and then to work centers within divisions. The measures of shop performance are mean flow-time, flow-time variance, and worker transfers between divisions and work centers. Labor control decisions prove to be important in their effect on both flow-time and labor transfer measures. In some cases labor control decisions are more important than dispatching decisions. The effects of dispatching decisions on flow-time measures are consistent with previous job shop research. Dispatching decisions also affect labor transfers.